Dosimetric characterization of the GammaClip™ 169Yb low dose rate permanent implant brachytherapy source for the treatment of nonsmall cell lung cancer postwedge resection. Issue 8 (15th July 2013) - Currier, Blake; Munro, John J.; Medich, David C.
Abstract : Purpose: : A novel 169 Yb low dose rate permanent implant brachytherapy source, the GammaClip™, was developed by Source Production & Equipment Co. (New Orleans, LA) which is designed similar to a surgical staple while delivering therapeutic radiation. In this report, the brachytherapy source was characterized in terms of "Dose calculation for photon‐emitting brachytherapy sources with average energy higher than 50 keV: Report of the AAPM and ESTRO" by Perez‐Calatayud et al. [Med. Phys. 39, – (2012)]10.1118/1.3703892 using the updated AAPM Task Group Report No. 43 formalism. Methods: : Monte Carlo calculations were performed using Monte Carlo N‐Particle 5, version 1.6 in water and air, the in‐air photon spectrum filtered to remove photon energies below 10 keV in accordance with TG‐43U1 recommendations and previously reviewed 169 Yb energy cutoff levels [D. C. Medich, M. A. Tries, and J. M. Munro, "Monte Carlo characterization of an Ytterbium‐169 high dose rate brachytherapy source with analysis of statistical uncertainty, " Med. Phys. 33, 163–172 (2006)]10.1118/1.2147767 . TG‐43U1 dosimetric data, including S K, D ̇ ( r, θ ), Λ, g L ( r ), F ( r, θ ), ϕ an ( r ), and ϕ ¯ a n were calculated along with their statistical uncertainties. Since the source is not axially symmetric, an additional set of calculations were performed to assess the resulting axial anisotropy. Results: : The brachytherapy source's dose rate constant was calculated to be (1.22 ± 0.03) cGy h −1 U −1 . The uncertainty in the dose to water calculations, D ̇ ( r, θ ), was determined to be 2.5%, dominated by the uncertainties in the cross sections. The anisotropy constant, ϕ ¯ a n, was calculated to be 0.960 ± 0.011 and was obtained by integrating the anisotropy factor between 1 and 10 cm using a weighting factor proportional to r −2 . The radial dose function was calculated at distances between 0.5 and 12 cm, with a maximum value of 1.20 at 5.15 ± 0.03 cm. Radial dose values were fit to a fifth order polynomial and dual exponential regression. Since the source is not axially symmetric, angular Monte Carlo calculations were performed at 1 cm which determined that the maximum azimuthal anisotropy was less than 8%. Conclusions: : With a higher photon energy, shorter half‐life and higher initial dose rate 169 Yb is an interesting alternative to 125 I for the treatment of nonsmall cell lung cancer.